Analisis Nilai-nilai Psikomotoris Dalam Alquran - Zulkifli, Zulkifli; Hamdi, Hafizul; Guslianto, Guslianto (Al-Ashri: Ilmu-Ilmu Keislaman, 2023)
Psychomotor skills are very important to be mastered at work, whether workers require energy or thought. Psychomotor in a theoretical perspective is Psychomotor Domain (Psychomotor Domain) contains behaviors that emphasize aspects of motor skills. Hierarki's Psychomotor Domain is as follows: imitate, manipulation, experience, and articulation. This research aims to analyze psychomotor values in the Quran. This research uses the study method literature. Literature studies are carried out by reading library sources to obtain the necessary data. The data sources used come from secondary data, the data was collected through textbooks, scientific journals, periodicals, ebooks, websites, statutory regulations, and other sources relevant to the research problem. The research results show that the words in the Alquran describe psychomotor values, with psychomotor or these skills, the interaction process can take place well because humans are creatures who cannot live alone and need other people, therefore interaction with language or speaking with good skills or psychomotor skills will become easier.